INDICATING UPLC METHOD FORQUANTIFICATION OF RELATED COMPOUNDS OF ACETYLSALICYLIC ACID IN IT`S SOLID DOSAGE FORM - RAO, V.VENKATESWARA; PRASAD, V.V.S.RAJENDRA; RAJU, M. BHAGAVAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
A simple, sensitive and specific UPLC method was developed for the identification and quantification of related compounds of aspirin from its solid dosage forms. The chromatographic separation employs the gradient elution using C18 column with the length of 100 mm x 2.1mm dimensions by using the solvent-A (containing mixture of water and orthophosphoric acid), solution-B (containing mixture of acetonitrile and methanol) with the flow rate of 0.4mL/min. All the analytes were detected and quantified at the wavelength of 237nm by using photo diode array detector. The method was validated as per ICH guidelines and found to be specific, precise, linear and accurate. This method has very lower limit of detection and limit of quantification. The peak purity obtained with all related compounds with the aid of photo diode array detector was satisfactory. Hence this method was concluded that stability indicating method. Key Words: Aceylsalicylic acid, Aspirin, Stability indicating UPLC method.